The common motifs of spring festivals in the slavic and turkic worlds: maslenitsa and nevruz - MEHTAP; TUĞBA (Uluslararası Türk Lehçe Araştırmaları Dergisi)
Festivals are national, religious, or special days or periods that reflect a nation’s history, beliefs, traditions, and culture. Festivals, which exist in every nation around the world, are the product of a long-standing history from the past to the present. The Slavic and Turkic peoples, whose origins date back to ancient times, have many festivals, including religious, national, seasonal, and cultural ones. These festivals are important elements that keep society together and ensure solidarity in society. Maslenitsa, celebrated as a seasonal festival among the Slavic people, and Nevruz, celebrated among the Turkic people, are festivals symbolizing the end of winter and the transition to spring. Maslenitsa is the oldest Russian festival that has survived to the present day. The tradition of celebrating Maslenitsa dates back to the pre-Christian period. Nevruz, described as the Turkish spring festival, is an old festival that dates back to before the Turks accepted Islam. This article will examine the common elements of Maslenitsa and Nevruz, two seasonal festivals with shared characteristics among two distinct nations.